Cation doping size effect for methane activation on alkaline earth metal doping of the CeO2 (111) surface. Issue 10 (5th January 2016) - Carey, J. J.; Nolan, M.
Abstract : Alkaline earth metal doping of CeO2 improves the dissociative adsorption of methane with the behaviour showing a correlation to dopant ionic radius. Abstract : Methane is an extremely important clean fuel source; however, its activation is extremely difficult due to the large energy required to break the first CH bond. This study presents a density functional theory investigation of doping of cerium dioxide (111) with alkaline earth metals to promote methane activation. The incorporatation of alkaline metals in the surface results in spontaneous formation of charge compensating oxygen vacancies, and thus enhances surface reducibility. This effect from substitutional doping of the ceria surface greatly improves the adsorption, and the stablity of the CH3 ˙ + H dissociation products compared undoped ceria. The enhanced stabilisation of the products drives the thermodynamics towards dissociation. The calculated kinetic barriers show that for Mg and Ca doped surfaces, the kinetic barrier is lowered compared to the undoped surface, while for Sr the activation energy is higher. We find a correlation between the thermodynamics and kinetics with the cation dopant size; the dissociation products become more stable with a decrease in dopant ionic radius while the kinetic barriers are reduced with increasing cation size up to the limit of the Ca cation. A smaller dopant ionic radius compared to that of CeO2 promotes methane activation, while doping with a larger ionic radius cation than the host diminishes the activity of the surface towards methane activation. The thermodynamics and kinetics that are affected from the dopant ionic radius show that consideration of the dopant size in a host oxide is needed for catalyst design. A simple descriptor for the reaction process is also developed arising from the relationship between the active oxygen vacancy formation and the stabilisation of the dissociation products.